Judicial review: an indirect appeal against the awards of the industrial court? / Khairunnisa Liyana Azani, Safiah @ Sofiezah Saflin and Sh.Norkatijah Zahir Khan Ali. - Azani, Khairunnisa Liyana; Saflin, Safiah @ Sofiezah; Zahir Khan Ali, Sh.Norkatijah (Faculty of Law, 2008)
This research is about the conflicting interest between a tribunal namely the Industrial Court and the High Court which granted by the supervisory jurisdiction. Some issues arouse within this matter as to whether the High Court has the right to interfere in the decision made by the Industrial Court, whether the Industrial Court has the right to stay with their decision based on the clause stipulated under Industrial Relation Act, whether the Industrial Court award is subject to be challenge on the ground other than error of law. We were asked to conduct this particular research in order to seek for the answer for the issues stipulated above. Some relevant steps have been taken such as conducting interviews with the professionals. It is actually quite hard for the research to be done. However, we have tried our very best to complete it. As a result, this project paper has been produced based on our own afford and co-operations.